An uncontrolled item of enterprise ICT innovation : the high-level digital divide - Pighin, Maurizio (Array, 2008)
Summary: The globalization phenomena strongly stresses western countries' economies. Especially in industrial districts, companies are reacting with continuous innovations in product and process, based mainly on the introduction of ICT. This continuous organizational change process forces employees to keep in touch with the working environment in an endless learning process. Therefore, the introduction of new ICT seems to bring a cultural development for individuals. Is this always true? Our conviction is that the strong ICT impact generates a new form of digital-divide, a "High-Level Digital Divide" (HLDD): an increasing cultural distance between people able to follow the enterprise ICT evolution and complexity, and people with a lower cultural growth ability. An uncontrolled growth of HLDD may limit the evolution capacity of the enterprise and drop out people from labor market